Niezamierzone skutki stosowania testów wysokiej stawki. Lekcja z amerykańskiej reformy NCLB - Zawistowska, Alicja (Studia Edukacyjne, 2020)
Educational decision makers willingly draw on solutions adopted in other countries. It was also the case in Polish educational reform started in late 90s. Since the introduction of the reform, Poland joined countries whose educational system is divided into three levels, each ending with an exit exams and core curriculum is set to teaching standards. The exams seem to be the most important element of the Polish reform. While the designers of educational policies are often inspired by the experiences of other countries during the planning phase, they are less willing to learn from them when it comes to predicting outcomes of the reform. A good case to analyze potential consequences of high-stakes testing is United States, where standardized tests have been administered since the beginning of the era of mass education. In this paper I will analyze the effects of the last, most controversial federal reform, commonly known as No Child Left Behind introduced in 2002. Findings of the study might be used to predict potential unintended effects of using the high stakes tests for accountability policy. The article addresses the problem of test scores inflation as well as the factors which may accelerate it.